Correlated lightning mapping array and radar observations of the initial stages of three sequentially triggered Florida lightning discharges. Issue 15 (15th August 2013) - Hill, J. D.; Pilkey, J.; Uman, M. A.; Jordan, D. M.; Rison, W.; Krebhiel, P. R.; I Biggerstaff, M.; Hyland, P.; Blakeslee, R.
Abstract : [1] Correlated Lightning Mapping Array and vertical‐scan radar images are presented for three rocket‐and‐wire triggered lightning flashes that occurred sequentially within 17 min in the presence of a decaying multicellular convective storm system over north‐central Florida. The initial stage (IS) of each flash propagated generally vertically to the altitude of the 0°C melting level, about 5 km, and then subsequently propagated for many kilometers horizontally along the melting level contour. Radar images suggest that the propagation paths of the IS channels below and above the melting level were heavily influenced by precipitation gradients. Flash UF 11‐24 exhibited a 12.6 km unbranched IS channel, the longest unbranched channel observed in the study by a factor of three. During flash UF 11‐25 (119 ms following the cessation of the measured IS current at ground and prior to the first return stroke), a natural cloud‐to‐ground discharge, perhaps induced by the IS, initiated between 2.5 and 4 km altitude and struck ground 5 to 7 km from the launching facility. The IS of flash UF 11‐26 propagated upward through a descending precipitation packet and apparently induced a naturally appearing bi‐level intracloud discharge via an upward‐negative leader that initiated within the IS breakdown region 3.5 km from the launching facility. The upward‐negative leader propagated from 5.6 to 9.3 km altitude in a time of 11 ms. The electrical current measured at ground during the IS of flash UF 11‐26 exhibited a 57 ms polarity reversal, transferring 19 C of positive charge to ground. Key Points: Correlated LMA and vertical‐scan radar images of Florida triggered lightning Correlation of IS breakdown path with radar‐determined precipitation gradients Rocket‐and‐wire triggering of a naturally appearing bi‐level IC discharge